Repeat catheter ablation for recurrent atrial fibrillation: Electrophysiologic findings and clinical outcomes. (15th February 2021) - Daimee, Usama A.; Akhtar, Tauseef; Boyle, Thomas A.; Jager, Leah; Arbab‐Zadeh, Armin; Marine, Joseph E.; Berger, Ronald D.; Calkins, Hugh; Spragg, David D.
Abstract: Introduction: Atrial fibrillation (AF) ablation is successful in 60%–80% of optimal candidates, with many patients requiring repeat procedures. We performed a detailed examination of electrophysiologic findings and clinical outcomes associated with first repeat AF ablations in the era of contact force‐sensing radiofrequency (RF) catheters. Methods: We retrospectively studied patients who underwent their first repeat AF ablations for symptomatic, recurrent AF at our center between 2013 and 2019. All repeat ablations were performed using contact force‐sensing RF catheters. Pulmonary vein (PV) reconnections at repeat ablation and freedom from atrial arrhythmia 1 year after repeat ablation were evaluated. We further assessed these findings based on AF classification at the time of presentation for repeat ablation, index RF versus cryoballoon (CB) ablation, and duration (≥3 versus <3 years) between index and repeat procedures. Results: Among 300 patients, there were 136 (45.3%) who presented for their first repeat ablations in persistent AF. During repeat ablation, at least one PV reconnection was found in 257 (85.6%) patients, while 159 (53%) had three to four reconnections. There was a similar distribution of reconnections among patients with persistent versus paroxysmal AF (mean: 2.7 ± 1.3 vs. 2.9 ± 1.2; p  = .341), index RF versus CB ablation (mean: 2.8 ± 1.3 vs. 2.9 ± 1.2; p  = .553), and ≥3 versus <3 years between index and repeat procedures (mean: 3.0 ± 1.1 vs. 2.7 ± 1.3; p  = .119). At repeat ablation, the PVs were re‐isolated in all patients, and additional non‐PV ablation was performed in 171 (57%) patients. Freedom from atrial arrhythmia at 1‐year follow‐up after repeat ablation was 66%, similar among those with persistent versus paroxysmal AF (65.4% vs. 66.5%; p  = .720), index RF versus CB ablation (66.7% vs. 68.9%; p  = .930), and ≥3 versus <3 years between index and repeat ablations (64.4% vs. 66.7%; p  = .760). Major complications occurred in a total of 4 (1.3%) patients. Conclusion: In a contemporary cohort of patients receiving their first repeat AF ablations using contact force‐sensing RF catheters, PV reconnections were common, and freedom from atrial arrhythmia was 66% at 1‐year follow‐up. The distributions of PV reconnections and rates of freedom from atrial arrhythmia were similar,  based on persistent versus paroxysmal AF at presentation for repeat ablation, index RF versus CB ablation, and duration between index and repeat procedures. The incidence of major complications was very low.